Enhancing cognitive and emotional English learning: a didactic proposal - Montes Granado, Consuelo (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
Ubiquitous learning as the emerging educational paradigm is giving rise to new virtual learning environments. The aim of this study is to contribute to this transformation in learning processes, with a specific focus on advancing English proficiency thanks to an innovative didactic design inspired by the concept of ‘personal learning environment’ (PLE), with the use of videos from YouTube. The findings highlight the potential value of PLEs and show how this design can be effective not only from a cognitive perspective but also as an emotional experience. This technique has also been of use to foster student autonomy and self-motivation.